PENGEMBANGAN BAHAN AJAR TEKS EKSPOSISI BERBASIS MULTILITERSI DI SMP - Ilman, Ilman; Syamsudduha, Syamsudduha (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2022)
Development of Multiliteration-Based Exposition Text Teaching Materials in Junior High School. This study aims to develop multiliterate-based exposition text teaching materials for class VIII junior high school students. This research is a research that uses research and development type. The research design used is an adaptation of the Dick & Carey development model. The data analysis technique was carried out by means of qualitative and quantitative descriptive and expert test data analysis using Aiken's formula. The results of this study are in the form of products, namely teaching materials in the form of textbooks which are categorized as very feasible. (1) The development of multiliterate-based exposition text teaching materials for class VIII SMP and equivalent is very important to meet the material needs of students in the 21st century education era and to overcome the weaknesses of the teaching materials used. (2) Based on the assessments of 3 experts, the teaching materials in the form of multiliterate-based exposition text books for grade VIII junior high school students are in the very appropriate category.